Arficial Intelligence Sebagai Mitra Belajar Mahasiswa: Mendorong Kreativitas Tanpa Mengabaikan Integritas Akademik - Salsa Putri Dilyandri; Nayla Putri Salsabila; Alya Sharliz; Reva Nur Rahmawati Guchi; Ahmad Hidayat Harahap; Parulian Sibuea (Takuana: Jurnal Pendidikan, Sains, dan Humaniora, 2026)
The development of Artificial Intelligence (AI) has brought significant changes to higher education, particularly in supporting student learning processes. This study aims to analyze the role of AI as a learning partner for students, examine its contribution to academic creativity, and identify the opportunities and challenges associated with maintaining academic integrity. This research employs a qualitative approach using a library research method by analyzing relevant journals, books, and scientific sources. The findings indicate that AI assists students in accessing information quickly, understanding learning materials, generating ideas, and improving learning effectiveness and efficiency. Furthermore, AI contributes to the development of academic creativity by providing diverse perspectives and supporting idea exploration processes. However, the use of AI also presents challenges, including the risks of plagiarism, technological dependency, and reduced critical thinking skills when used irresponsibly. Therefore, AI should be utilized ethically and responsibly as a supportive tool that enhances learning without replacing students' intellectual roles. This study highlights the importance of balancing technological utilization with the principles of academic integrity in higher education.